An Investigation on the Implementation of the Learning Cycle 5E to Improve Student Activeness - Ningrum, Elinda Puspita; Martini; Purnomo, Aris Rudi (Science Education and Application Journal, 2024)
An Investigation on the Implementation of the Learning Cycle 5E to Improve Student Activeness. This research aims to investigate the implementation of the learning Cycle 5E model in improving student activeness. The objects of this research are scientific works in the form of journal articles and research results. The research method employed is a literature review through analyzed journals. The technique used involves analyzing three pieces of literature on the Learning Cycle 5E to assess the impact of this model on student activeness in the learning process. The analysis results indicate that each phase of the Learning Cycle 5E model can improve student activeness during the learning process. Based on the three studies, from Cycle I to Cycle II, there is a noted increase in the average student activeness: Researcher 1 experienced a 3.35% increase, Researcher 2 saw an 8.17% increase, and Researcher 3 had a 15.84% increase. Future research should consider comparative studies of the Learning Cycle 5E model with other pedagogical approaches, longitudinal assessments of its long-term effects, and investigations into its application across diverse educational settings and technology integration.